Possible effects of the total solar eclipse of August 11, 1999 on the geomagnetic field variations over Elazig-Turkey - Özcan, O; Aydogdu, M (Pergamon-Elsevier Science Ltd, 2004)
In this paper, the variations of the magnetic field, due to current flowing in the ionospheric E-region over Elazig-Turkey during the August 11, 1999 total solar eclipse have been computed. It is shown that the solar eclipse has no significant effects on the north-south component of the magnetic field. However, the westward component of the magnetic field is decreased by the solar eclipse. Therefore, we would expect that the change in the magnetic field in E-region during the solar eclipse would modify the geomagnetic field at ground level. (C) 2004 Elsevier Ltd. All rights reserved.
Keywords: solar eclipse; E-region; current density; geomagnetic variations